Outcome of ondansetron on subarachnoid block-induced hypotension in infraumbilical surgeries - Renganathan S; Navin C; Ganesh Prabhu SC (Asian Journal of Medical Sciences)
Background: Bradycardia and hypotension are common post-subarachnoid block (SAB) complications that can result in adverse outcomes. The 5-HT3 receptor antagonist ondansetron, which is often used as an antiemetic, has recently been studied for its possible effect on preserving hemodynamic stability during SAB.